Pendidikan Akuntansi dan Perempuan: Dari Ideologi Patriarki ke Praktik Pemujaan Tubuh - Tjiptohadi Sawarjuwono; Anantawikrama T. Atmadja (Jurnal Akuntansi dan Auditing Indonesia, 2005)
The patriarch culture which apply to balinese society nowadays slowly fade away. Equal formal education values between male and female indicate this degradation. Parents are giving their daughters freedom to seek education. When related to the field of accounting, Balinese women pay more interest compared to Balinese men. It is well-known that accounting is consi¬dered a masculine field of study. Data acquired from a Balinese university show that the number of female students in the department of accounting is greater than male students. This essay attempts to seek the reason why women choose accounting, whether there are any parental influences or of personal desire, and whether gender ideologies have a role in their decision. There are a few reasons which support parental choice and balinese women's decision. First of all, education boosts social status. Second, accounting profession suits the women’s job. Third, short study period, smaller investment in terms of money, and have greater job opportunity. Through D3 Accounting Educational Degree Program Balinese women gain more values, intelec¬tually, economically, and politically therefore having greater bargaining power towards their envi¬ronment.Keywords:    Balinese women's role, Patriarch culture, Accounting education, Accounting's role